Habitar o espaço doméstico: intervenções nas casas-tipo do conjunto habitacional Privê Atlântico - Milagre, Carolina Vivas da Costa (2021)
Dwelling corresponds to the action of appropriating space by man, at a certain time. According to Lefebvre's thoughts, capital transforms living into habitat, reducing space to its primary function and depriving i t of its social, symbolic and cultural dimension, as it considers it as a product.Thus, this research focuses on the discussion of the house, understanding it as a social space, in order to reveal the contradictions between dwelling and habitat. The objects of study are the houses of the Privê Atlântico housing/gated community, located in Goiânia. Privê Atlântico originated as a housing in 1978, with standard houses, which have possibilities for expansion and are intended for the lower middle class. The design of these houses was conceived by architects Silas Varizo and Edeni Reis da Silva, within the context of modern architecture, produced i n Brazil at that time. Therefore, the houses were configured from a new way of living i n the domestic space. Today, this housing is characterized as a gated community and these residences have undergone major transformations, both physical, such as the insertion of new spaces, reconfigurations and demolitions, as well as subjective, due to the new ways of living and the specific spaces of each resident. To analyze the material modifications of single-family homes, conceived from standard projects, it is based on the concepts of graphic analysis, from which the relevant aspects are extracted, starting from the visualization of the fundamental elements of the formal and spatial design resulting from the interventions. In relation to immaterial changes, the space is analyzed through a sociological view to discuss the sociocultural aspects and the daily actions reflected in the domestic space, understood from the interviews with the dwellers. Thus, the contradictions between dwelling and habitat in the studied homes are revealed. It is noticed that the two configurations of Privê Atlântico, as a housing and as a gated community, compromise the dwelling. First, because the houses were built on the city's margins, unrelated to urban life and later for the construction of the wall, contributing to socio-spatial segregation.Still, the houses show nuances of dwelling, due to the architectural quality of the original project, which allowed interventions and enabled social, symbolic and cultural representations in their domestic space: traditional ways of living are resumed and merged with modern habits on the domestic spaces, as well they correspond to the daily life of each family, also the appropriation of public spaces in the gated community is evident. In this context, this research contributes to other discussions about home, based on the study of domestic space through social relations and dwellers' narratives.